Single-shot two-dimensional nano-size mapping of fluorescent molecules by ultrafast polarization anisotropy imaging - Wang, Peng; Mishra, Yogeshwar Nath; Bauer, Florian; Gudipati, Murthy S.; Wang, Lihong V. (Nature Communications, 2025)
Molecular size plays a crucial role in determining the physical, chemical, and biological properties of substances. However, traditional fluorescence polarization anisotropy methods struggle to capture fast transient processes or provide plane-specific details. To overcome these limitations, we introduce Compressed Ultrafast Planar Polarization Anisotropy Imaging (CUP2AI). This approach combines femtosecond laser-sheet illumination, molecular rotational diffusivity, and compressed sensing to enable real-time, non-invasive, wide-field anisotropy measurements in both liquid and gas phases. CUP2AI captures 2D molecular size mapping in a single acquisition, granting unprecedented insights into dynamic events across various excitation modes (i.e. both one- and two-photon) and environmental conditions. It enables mapping of molecular volume (500 Å³–80,000 Å³) and hydrodynamic diameter (10 Å–50 Å) based on anisotropy lifetimes. We imaged fluorescein-conjugated dextran in water and polycyclic aromatic hydrocarbons in flames. CUP2AI holds transformative potential for applications ranging from molecular biology and drug design to nanoparticle formation.
CRIS-Team Scopus Importer:2025-06-06